Neurobiology of Parental Regulation of the Infant and Its Disruption by Trauma Within Attachment - Graf, Nina; Zanca, Roseanna M.; Song, Wei; Zeldin, Elizabeth; Raj, Roshni; Sullivan, Regina M. (Frontiers in Behavioral Neuroscience, 2022)
The complex process of regulating physiological functions and homeostasis during external and internal disruptions develops slowly in altricial species, with parental care functioning as a co-regulator of infant physiological and emotional homeostasis. Here, we review our current understanding of the infant’s use of parental behaviors for neurobehavioral regulation and its disruption with harsh parental care. Taking a cross-species view, we briefly review the human developmental literature that highlights the importance of the caregiver in scaffolding the child’s physiological and emotional regulation, especially under threat and stress. We then use emerging corresponding animal literature within the phylogenetically preserved attachment system to help define neural systems supporting caregiver regulation and its supporting causal mechanism to provide translational bridges to inform causation and mechanisms impossible to define in children. Next, we briefly review animal research highlighting the impact of specific sensory stimuli imbedded in parental care as important for infant physiological and emotion regulation. We then highlight the importance of parental sensory stimuli gaining hedonic value to go beyond simple sensory stimuli to further impact neurobehavioral regulation, with poor quality of care compromising the infant’s ability to use these cues for regulation. Clinically, parental regulation of the infant is correlated with later-life neurobehavioral outcome and quality of life. We suggest an understanding of this parental regulation of the infant’s immediate neurobehavioral functioning within the context of attachment quality, that may provide insights into the complex processes during early life, initiating the pathway to pathology.